Hydrogenated Cs2AgBiBr6 for significantly improved efficiency of lead-free inorganic double perovskite solar cell - Zhang, Zeyu; Sun, Qingde; Lu, Yue; Lu, Feng; Mu, Xulin; Wei, Su-Huai; Sui, Manling (Nature communications, 2022)
Development of lead-free inorganic perovskite material, such as Cs 2 AgBiBr 6 , is of great importance to solve the toxicity and stability issues of traditional lead halide perovskite solar cells. However, due to a wide bandgap of Cs 2 AgBiBr 6 film, its light absorption ability is largely limited and the photoelectronic conversion efficiency is normally lower than 4.23%. In this text, by using a hydrogenation method, the bandgap of Cs 2 AgBiBr 6 films could be tunable from 2.18 eV to 1.64 eV. At the same time, the highest photoelectric conversion efficiency of hydrogenated Cs 2 AgBiBr 6 perovskite solar cell has been improved up to 6.37% with good environmental stability. Further investigations confirmed that the interstitial doping of atomic hydrogen in Cs 2 AgBiBr 6 lattice could not only adjust its valence and conduction band energy levels, but also optimize the carrier mobility and carrier lifetime. All these works provide an insightful strategy to fabricate high performance lead-free inorganic perovskite solar cells. Though inorganic perovskites are an attractive, non-toxic and stable alternative to organic-inorganic halide perovskite solar cells, realizing efficient devices remains a challenge. Here, the authors report hydrogenated lead-free inorganic perovskite solar cells with enhanced power conversion efficiency.